TEXNOLOGIYA MAShG’ULOTLARIDA O‘QUVChILARGA EKOLOGIK TA’LIM-TARBIYA BERIShDA KOMPYUTER TEXNOLOGIYALARI VA INTERFAOL METODLARDAN FOYDALANISh TEXNOLOGIYALARI - Tajiyev, J.K.; Kuryozova, M.R. (SCIENCE and SOCIETY, 2025)
The article discusses the importance of modern information and communication technologies (ICT) and interactive methods in the formation of environmental education in students during technology classes, the methods of their effective application, the possibilities of developing ecological culture and environmental awareness through practical activities in the development of lesson plans and project work.